2022
DOI: 10.3390/app12115636
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Android Sensors and Google Earth in Pavement Maintenance Management Systems for Developing Countries

Abstract: Governments and road agencies face the challenging task of maintaining roads. One of the reasons this is challenging is that the maintenance process requires utilizing a substantial amount of road network condition data. There are many approaches for measuring road surface conditions which are very costly and time-consuming, as well as requiring skillful operators. Developing countries have limited budgets for planning and monitoring road maintenance. This research aims to establish a low-cost pavement mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…An Internet-of-Things approach was suggested that used sensors in the pavement which indicated its state in real time [7]. Low-cost methodologies and indicators installed on smartphones are applied for road diagnostics in developing countries [8]. Most of these approaches cannot be implemented in the republic of Kazakhstan, as there is lack of both financial and human resources for detailed field diagnostics of huge lengths of road.…”
Section: Introductionmentioning
confidence: 99%
“…An Internet-of-Things approach was suggested that used sensors in the pavement which indicated its state in real time [7]. Low-cost methodologies and indicators installed on smartphones are applied for road diagnostics in developing countries [8]. Most of these approaches cannot be implemented in the republic of Kazakhstan, as there is lack of both financial and human resources for detailed field diagnostics of huge lengths of road.…”
Section: Introductionmentioning
confidence: 99%